Improving Interior Design: Topology Optimization and Large-Scale 3D Printing Plastic - Tchuigwa Paulin Faskel Tchoundie; Sýsová Katěrina (Technical Transactions)
The pervasive use of plastics, despite their economic benefits in recycling and reuse due to their low cost and abundance, has contributed significantly to global environmental issues, including pollution and global warming. Notably, polymer production continues to rise, paralleling increasing environmental impacts. This paper shifts focus from these broader environmental concerns to explore how topology optimization and advanced 3D printing technologies are transforming interior design. Specifically, it examines the integration of topology optimization a technique traditionally used in engineering to distribute materials efficiently within a design space to enhance both the sustainability and creativity of large-scale 3D printing applications in interior design. By optimizing material usage and minimizing waste, these technologies not only address some environmental concerns associated with plastics but also revolutionize how designers conceive and implement interior spaces. The paper highlights case studies where these integrated technologies have enabled unprecedented levels of creativity and efficiency, redefining the aesthetics and functionality of interior environments.